Validation of a Standard Protocol to Assess the Fermentative and Chemical Properties of Saccharomyces cerevisiae Wine Strains - Romano, Patrizia; Siesto, Gabriella; Capece, Angela; Pietrafesa, Rocchina; Lanciotti, Rosalba; Patrignani, Francesca; Granchi, Lisa; Galli, Viola; Bevilacqua, Antonio; Campaniello, Daniela; Spano, Giuseppe; Caridi, Andrea; et al. (Frontiers in Microbiology, 2022)
This paper reports on a common experiment performed by 17 Research Units of the Italian Group of Microbiology of Vine and Wine (GMVV), which belongs to the Scientific Society SIMTREA, with the aim to validate a protocol for the characterization of wine strains of Saccharomyces cerevisiae. For this purpose, two commercial S. cerevisiae strains (EC 1118 and AWRI796) were used to carry out inter-laboratory-scale comparative fermentations using both synthetic medium and grape musts and applying the same protocol to obtain reproducible, replicable, and statistically valid results. Ethanol yield, production of acetic acid, glycerol, higher alcohols, and other volatile compounds were assessed. Moreover, the Fourier Transform Infrared Spectroscopy was also applied to define the metabolomic fingerprint of yeast cells from each experimental trial. Data were standardised as unit of compounds or yield per gram of sugar (glucose and fructose) consumed throughout fermentation, and analysed through parametric and non-parametric tests, as well as multivariate approaches (cluster analysis, two-way joining, and Principal Component Analysis). The results of experiments carried out by using synthetic must showed that it was possible to gain comparable results from three different laboratories by using the same strains. Then, the use of the standardised protocol on different grape musts allowed pointing out the goodness and the reproducibility of the method; it showed the main traits of the two yeast strains and allowed reducing variability amongst independent batches (biological replicates) to acceptable levels. In conclusion, the findings of this collaborative study contributed to the validation of a protocol in a specific synthetic medium and in grape must and showed how data should be treated to gain reproducible and robust results, which could allow direct comparison of the experimental data obtained during the characterization of wine yeasts carried out by different research laboratories.